Teologi Pernikahan Kristen Sebagai Kritik Etis Teologis Terhadap LGBT - James Lola (KAMASEAN: Jurnal Teologi Kristen, 2020)
One of the issues that has become the subject of debate theologically or ethically is LGBT, through literature research, the author tries to provide an understanding of Christian marriage theology that is in accordance with Bible principles to be used as a criticism of the views that accept LGBT to be legalized in the Church.